2004
DOI: 10.1002/ppul.10416
|View full text |Cite
|
Sign up to set email alerts
|

BPI‐ANCA of pediatric cystic fibrosis patients can impair BPI‐mediated killing of E. coli DH5α in vitro

Abstract: Gram-negative bacterial lung infections and chronic bacterial colonization are major threats for pediatric cystic fibrosis (CF) patients. Besides impeded mucociliary clearance, other mechanisms that contribute to increased susceptibility to infections are presumed. The bactericidal/permeability-increasing protein (BPI), which is delivered by neutrophil granulocytes and mucosal epithelial cells, is one of the most potent innate antibiotics against Gram-negative bacteria and endotoxin. Antineutrophil cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…Epitope mapping data have revealed similarities of BPI epitopes recognized by BPI-ANCA (Table 1) with specific protein sequences of infecting GNB (e.g. outer membrane proteins of Pseudomonas aeruginosa) suggesting that cross-reactivity followed by epitope spreading in the inflammatory setting could be a mechanism for broken tolerance against BPI [118,119]. The waning of BPI-ANCA in CF patients after lung transplantation and a reduced pulmonary burden of P. aeruginosa [120,121] is consistent with this hypothesis.…”
Section: Autoimmunity Against Bpi: Bpi-ancasupporting
confidence: 69%
See 2 more Smart Citations
“…Epitope mapping data have revealed similarities of BPI epitopes recognized by BPI-ANCA (Table 1) with specific protein sequences of infecting GNB (e.g. outer membrane proteins of Pseudomonas aeruginosa) suggesting that cross-reactivity followed by epitope spreading in the inflammatory setting could be a mechanism for broken tolerance against BPI [118,119]. The waning of BPI-ANCA in CF patients after lung transplantation and a reduced pulmonary burden of P. aeruginosa [120,121] is consistent with this hypothesis.…”
Section: Autoimmunity Against Bpi: Bpi-ancasupporting
confidence: 69%
“…In contrast, BPI bound endotoxin is not accessible for LBP/CD14 mediated LOS/LPS extraction and does not cause an inflammatory response in monocytes [81,82,107]. Shown is the prevalence of BPI-ANCA in selected studies of healthy persons and patients with infectious diseases, rheumatic diseases, inflammatory bowel diseases and immunodeficiency [17,18,115,118,119,126]. Abbreviations: HIV human immunodeficiency virus; ReA reactive arthritis; TAP transporter associated with antigen presentation…”
Section: Figure 4 Roles Of Bpi During Gnb Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that BPI plays a crucial role during P. aeruginosa lung infections in CF patients (8,23,24,22). Nevertheless, to date, there are no data available on the expression of BPI in the infected lungs of CF patients.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, a mouse ortholog of human BPI was described, indicating the importance of this antimicrobial protein throughout evolution in different vertebrate species (7). Antineutrophil cytoplasmic autoantibodies against BPI (BPI-ANCA) have been found in up to 90% of CF patients (22,28), and the presence of BPI-ANCA has been shown to correlate with chronic P. aeruginosa lung infection (1,6) and Pseudomonas-induced lung damage (4). In vitro, BPI-ANCA have been shown to inhibit neutrophil-mediated killing of P. aeruginosa (24).…”
mentioning
confidence: 99%